The robust estimators of reliability function using sample technique AM & POT - فدعم انتصار عريبي; نور ورود باسم (Journal of Economics and Administrative Sciences, 2019)
Abstract The Phenomenon of Extremism of Values ​​(Maximum or Rare Value) an important phenomenon is the use of two techniques of sampling techniques to deal with this Extremism: the technique of the peak sample and the maximum annual sampling technique (AM) (Extreme values, Gumbel) for sample (AM) and (general Pareto, exponential) distribution of the POT sample. The cross-entropy algorithm was applied in two of its methods to the first estimate using the statistical order and the second using the statistical order and likelihood ratio. The third method is proposed by the researcher. The MSE comparison coefficient of the estimated parameters and the probability density function for each of the distributions were calculated in addition to the estimation of the reliability function in two methods: the first when the sample is complete and the second when the sample is divided: (MSE) for the reliability function for the complete sample and the divided sample.